NILAI-NILAI SEJARAH DAN BUDAYA DALAM LANSKAP KAWASAN PADUSAN SEBAGAI WARISAN LOKAL - Indah Amalia; Adinda Putri Fandriya; Suci Aini Salsabila; Mayla Indah Prihar Anggraini; Warodil Aqwalil Auliya; Aisyah Firly Wulan Januari; Sugiantoro Sugiantoro (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Padusan in Pacet District, Mojokerto Regency represents a cultural landscape formed through long-term historical interactions between humans and the environment. This landscape not only reflects its physical characteristics but also embodies symbolic meanings, historical values, and cultural practices preserved within the community’s collective memory. These values are reflected in Grenjengan Waterfall as a cultural space perceived as a sacred water source, the Mbah Melati shrine as a center of spiritual activities, and the Padusan hot spring which demonstrates the continuity of natural resource utilization. These elements illustrate the interconnection of ecological, social, and cultural dimensions that shape local identity. This study employs a qualitative approach. The findings indicate a transformation of the landscape’s function from a sacred and utilitarian space into a tourism destination oriented toward recreational and economic interests, leading to a reduction in its historical and cultural meanings. Nevertheless, the multidimensional historical values remain preserved and hold potential to be developed as a foundation for educational-based tourism that strengthens local identity and cultural sustainability. ABSTRAK Padusan di Kecamatan Pacet, Kabupaten Mojokerto merupakan lanskap budaya yang terbentuk melalui interaksi historis antara manusia dan lingkungan. Lanskap ini tidak hanya mencerminkan aspek fisik, tetapi juga memuat nilai simbolik, historis, serta praktik budaya dalam memori kolektif masyarakat. Nilai tersebut tercermin pada Air Terjun Grenjengan sebagai ruang kultural yang dimaknai sebagai sumber air sakral, Punden Mbah Melati sebagai pusat aktivitas spiritual, serta pemandian air panas Padusan yang menunjukkan kesinambungan pemanfaatan sumber daya alam. Ketiga elemen tersebut merepresentasikan keterkaitan dimensi ekologis, sosial, dan kultural yang membentuk identitas lokal. Penelitian ini menggunakan pendekatan kualitatif. Temuan penelitian menunjukkan adanya transformasi fungsi lanskap dari ruang sakral dan utilitarian menjadi destinasi wisata yang berorientasi rekreatif-ekonomi, yang berdampak pada reduksi makna historis dan kultural. Meskipun demikian, nilai sejarah yang bersifat multidimensional masih bertahan dan berpotensi dikembangkan sebagai dasar pariwisata berbasis edukasi yang memperkuat identitas lokal dan keberlanjutan budaya.